Penyuluhan Membumikan Kesadaran Anti Bullying dalam Perspektif Profil Pelajar Pancasila di Desa Sukorejo Kabupaten Pemalang - Rengga Kusuma Putra; Dian Karisma; Maulana Fahmi Idris (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Bullying behavior or actions that occur among adolescents have a negative impact on victims and society. Teenagers tend to behave aggressively by bullying others, so that the victim is very intimidated, even greatly affecting the victim's physical and psychological health. The lack of awareness of students, parents, teachers and even the community makes this bullying action increase, so it is necessary to conduct socialization to increase anti-bullying awareness by applying the Pancasila student profile. The targets in this socialization activity are students, parents, teachers and the community in Sukorejo Village, Pemalang Regency. The purpose of this socialization activity is to provide understanding and legal knowledge about anti-bullying awareness, especially among adolescents or students, given the emotional development that affects attitudes and actions in a more aggressive direction. This socialization activity uses an approach method by involving the audience by interacting through discussion and question and answer, which is then evaluated for feedback from the audience, and analyzed in the form of a journal so that it can be useful and for learning for the wider community.